2016
DOI: 10.1111/ina.12321
|View full text |Cite
|
Sign up to set email alerts
|

Exhaust ventilation in attached garages improves residential indoor air quality

Abstract: Previous research has shown that indoor benzene levels in homes with attached garages are higher than homes without attached garages. Exhaust ventilation in attached garages is one possible intervention to reduce these concentrations. To evaluate the effectiveness of this intervention, a randomized crossover study was conducted in 33 Ottawa homes in winter 2014. VOCs including benzene, toluene, ethylbenzene, and xylenes, nitrogen dioxide, carbon monoxide, and air exchange rates were measured over four 48-hour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 30 publications
2
16
0
Order By: Relevance
“…In a house, an attached garage can be a significant contaminant contributor to the indoor environment without a furnace, let alone with one [4][5][6][7][8][9][10][11][12]. The contaminants from a starting car or chemicals alone can influence the air quality within an attached household.…”
Section: Introductionmentioning
confidence: 99%
“…In a house, an attached garage can be a significant contaminant contributor to the indoor environment without a furnace, let alone with one [4][5][6][7][8][9][10][11][12]. The contaminants from a starting car or chemicals alone can influence the air quality within an attached household.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, create negative pressure in production areas to prevent the flow of airborne contaminants out of the source area. A 2017 study showed that negative pressure created by exhaust fans in attached residential garages reduced VOC concentrations inside the home by 50% (Mallach et al 2017). A push-pull ventilation could be added to LEV systems to improve efficiency (Leung, Liu, and Chan 2005).…”
Section: Recommendations For Managementmentioning
confidence: 99%
“…However, this strategy is risky to be applicable in the classroom since people are around. In the other hand, the exhaust fan was able to reduce the dust and unhealthy gas in the factory by improving the air circulating in that room 10 . Herein, we demonstrate the utilization of exhaust fan to improve the air-conditioned indoor air quality.…”
Section: Introductionmentioning
confidence: 99%